DRAMA TARI TOPENG BONDRES SEBAGAI MEDIA PENERANGAN HINDU - Parmajaya I Putu Gede (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2017)
Mask Bondres whose development began in the nineties did get its own place for the people of Bali. Displays the dance plays that are unit and not tied to a grip of dance or storyline. Mask performing art displays funny figures, with fresh humor sometimes inserted social satire or confessional ailments that occur in society. But sometimes it also conveys moral ethical messages by taking philosophies or pitutur-pitutur originating from Hindu Religion in particular.Topeng Bondres is unique in which combine dance, drama and gamelan art. In addition to displaying funny figures, with fresh humor sometimes in selipi satire of social idiosyncrasies or konilik that occurred in the community. But sometimes also convey moral ethical messages by taking philosophy-philosophy or pitutur-originated from Hindu Religion in particular.Keywords: Dance, Bondres, Media